An Investigation on the Lasting Impact of COVID-19 on Hope, Gratitude, and Forgiveness of College Students' Wellbeing - Pushpalatha, A. P.; Jeya Jeevakani, G.; Bojiah, Janaki (Journal of Engineering Education Transformations, 2025)
With the COVID-19 widespread, the disruption of the normal routine of the people global wide was predominant. The restrictions abiding the control of the spread of the pandemic were effective in controlling the spread of the virus, but it has remained instrumental in the upheavals of negative emotions amidst the people even after the pandemic period. Most significantly, these protocols have impacted the college students socially and emotionally. To sustain the sense of happiness as well as fulfilment in life, hope, forgiveness, and gratitude are the significant contributors. This study investigated the impact of hope, forgiveness, and gratitude on the college students in the post pandemic era using the Hope Scale, the Gratitude Questionnaire, and the Heartland Forgiveness Scale to collect data. Quantitative analysis was carried out using SPSS; t-tests and ANOVA tests enabled the analysis resulting in the findings that the parents and teachers should encourage pupils to develop good habits and attend specialized trainings on cultivating hope, forgiveness, and gratitude to raise their degree of optimism and wellbeing.